NaClO‐Mediated Cross Installation of Indoles and Azoles Benefits Anticancer Hit Discovery. (18th January 2023) - Yu, Changjun; E., Ruiyao; Zhang, Xiao‐Wei; Hu, Wen‐Qian; Bao, Guangjun; Li, Yiping; Liu, Yuyang; He, Zeyuan; Li, Jingyue; Ma, Wen; Mou, Ling‐Yun; Wang, Rui; et al.
Abstract: Innovations in synthetic chemistry have a profound impact on the drug discovery process, and will always be a necessary driver of drug development. As a result, it is of significance to develop novel simple and effective synthetic installation of medicinal modules to promote drug discovery. Herein, we have developed a NaClO‐mediated cross installation of indoles and azoles, both of which are frequently encountered in drugs and natural products. This effective toolbox provides a convenient synthetic route to access a library of N‐linked 2‐(azol‐1‐yl) indole derivatives, and can be used for late‐stage modification of drugs, natural products and peptides. Moreover, biological screening of the library has revealed that several adducts showed promising anticancer activities against A549 and NCI‐H1975 cells, which give us a hit for anticancer drug discovery. Abstract : A rapid, effective NaClO‐mediated cross installation of indoles and azoles for the construction of various N‐linked 2‐(azol‐1‐yl) indole derivatives and the late‐stage functional modification of drugs and peptides has been developed, which can benefit anticancer hit discovery.